2016
DOI: 10.1038/srep27021
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression analysis using RNA-seq uncovered a new role for SR1/CAMTA3 transcription factor in salt stress

Abstract: Abiotic and biotic stresses cause significant yield losses in all crops. Acquisition of stress tolerance in plants requires rapid reprogramming of gene expression. SR1/CAMTA3, a member of signal responsive transcription factors (TFs), functions both as a positive and a negative regulator of biotic stress responses and as a positive regulator of cold stress-induced gene expression. Using high throughput RNA-seq, we identified ~3000 SR1-regulated genes. Promoters of about 60% of the differentially expressed gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 53 publications
4
50
0
Order By: Relevance
“…Massive immune activation in camta3‐ knockout plants (at 19–21°C) led to the notion that CAMTAs act as negative regulators of immunity (Du et al ., ; Nie et al ., ). camta3‐ knockout plants constitutively express multiple biotic/abiotic stress‐responsive genes (except cold‐responsive genes) and exhibit salt tolerance (Prasad et al ., ). Virus‐induced gene silencing of CAMTAs in tomato also results in constitutive defense activation and enhanced pathogen resistance, albeit at the cost of drought tolerance (Li et al ., ).…”
Section: Environmental Effects On Plant Immunitymentioning
confidence: 97%
“…Massive immune activation in camta3‐ knockout plants (at 19–21°C) led to the notion that CAMTAs act as negative regulators of immunity (Du et al ., ; Nie et al ., ). camta3‐ knockout plants constitutively express multiple biotic/abiotic stress‐responsive genes (except cold‐responsive genes) and exhibit salt tolerance (Prasad et al ., ). Virus‐induced gene silencing of CAMTAs in tomato also results in constitutive defense activation and enhanced pathogen resistance, albeit at the cost of drought tolerance (Li et al ., ).…”
Section: Environmental Effects On Plant Immunitymentioning
confidence: 97%
“…CAMTA6 (SR3) transcript levels were reported to be enhanced by salt in 3-week-old Col-0 plants (Yang and Poovaiah, 2002). Prasad et al (2016) suggested that CAMTA3 (SR1) acts as a negative regulator of salt tolerance. However, the expression pattern during the early stages of germination, under control and salt stress conditions, has not been reported.…”
Section: Camta6 Expression Is Enhanced By Salt During Germinationmentioning
confidence: 99%
“…To further validate the intermediate TF network that regulates RAO7/MYB29-affected genes, we gathered published microarray studies on loss-and/or gain-offunction mutants for ATAF2, ATWRKY11, WRKY15, WRKY33, WRKY40, and SR1 (Delessert et al, 2005;Journot-Catalino et al, 2006;Birkenbihl et al, 2012;Vanderauwera et al, 2012;Van Aken et al, 2013;Prasad et al, 2016). For each TF, DE genes were split into groups of up-and down-regulated genes under control and stress conditions.…”
Section: Downstream Transcriptional Regulatory Network Analysis Reveamentioning
confidence: 99%